Answer:
C.2:4
Step-by-step explanation:
1*2=2
3*2=6
2:6=2:4
|
|
|
not true so it is C.
Answer:
y = x² − 6x − 27
Step-by-step explanation:
To distribute, you can use something called FOIL. It stands for First, Outer, Inner, Last.
First, multiply the First term in each factor.
x · x = x²
Now multiply the Outer terms in each factor.
x · 3 = 3x
Next multiply the Inner terms in each factor.
-9 · x = -9x
Finally, multiply the Last terms in each factor.
-9 · 3 = -27
Add them all up:
x² + 3x − 9x − 27
x² − 6x − 27
No, it is not a function, since 6 is repeating itself and the x should never repeat if it’s a function.
1 and 3 only answer is number 2